(untitled) (Fiep Bulletin - online, 2016)
This research study has elements which were obtained through testing to verify neuromuscular conditions of certain muscle groups of the body, the excellence order neuromuscular fitness. In this step, the study investigates the different levels of neuromuscular fitness distinct periods of the course Bachelor of Physical Education Integrated School of Patos-PB (FIP). The study was conducted in bodybuilding gym Fip Fitness of the Faculty, so there was no use of different machines or outside the vestments of the inclusion criteria. Before the survey analyzes the results showed no significant difference between the times of the 1st and the 8th. The study was conducted with 37 students from both periods properly enrolled in the course. The study found no difference between the neuromuscular fitness levels of students who are entering the course and those completing the course.